Pengaruh Consumer Animosity terhadap Brand Loyalty dengan Boycott Participation dan Product Judgment sebagai Variabel Intervening: Studi pada Konsumen Starbucks di Pulau Jawa - Hasna Hanan Ariqoh; Mahfudz Mahfudz (Diponegoro Journal of Management, 2026)
This study was prompted by growing consumer animosity in Indonesia due to global geopolitical issues, which triggered a boycott participation against various international brands, including Starbucks. This condition has the potential to significantly affect consumer loyalty. This study aims to analyze the effect of consumer animosity on brand loyalty with boycott participation and product judgment as intervening variables among Starbucks consumers in Java Island.This study uses a quantitative method with a Structural Equation Model (SEM) approach and data processing is carried out through AMOS. Data collection uses a non-probability sampling method with a purposive sampling tehnique through the distribution of questionnaires directly to Starbucks consumers in Java Island. The number of samples obtained was 127 respondents who met the research criteria. The test result show that the overall goodness of fit is in the good category.The results of the study show that all hypotheses were accepted. This study found that consumer animosity has a significant positive effect on boycott participation and a significant negative effect on product judgment. In addition, boycott participation has a significant negative effect on brand loyalty, while product judgment has a significant positive effect on brand loyalty. These findings confirm that boycott participation and product judgment act as mediators in the relationship between consumer animosity and brand loyalty, so that the stronger the feelings of consumer animosity, the lower the level of loyalty to Starbucks.